2017
DOI: 10.1002/cncr.30623
|View full text |Cite
|
Sign up to set email alerts
|

Progression‐free survival of children with localized ependymoma treated with intensity‐modulated radiation therapy or proton‐beam radiation therapy

Abstract: BACKGROUND: The treatment for childhood intracranial ependymoma includes maximal surgical resection followed by involved-field radiotherapy, commonly in the form of intensity-modulated radiation therapy (IMRT). Proton-beam radiation therapy (PRT) is used at some centers in an effort to decrease long-term toxicity. Although protons have the theoretical advantage of a minimal exit dose to the surrounding uninvolved brain tissue, it is unknown whether they have the same efficacy as photons in preventing local rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 30 publications
2
41
0
4
Order By: Relevance
“…Serious toxicity was limited and no unexpected side effects were observed. Specifically, the rates of symptomatic brainstem necrosis and vasculopathy in this cohort were comparable to reports of children treated with photons over the past 5 years …”
Section: Discussionsupporting
confidence: 72%
“…Serious toxicity was limited and no unexpected side effects were observed. Specifically, the rates of symptomatic brainstem necrosis and vasculopathy in this cohort were comparable to reports of children treated with photons over the past 5 years …”
Section: Discussionsupporting
confidence: 72%
“…Historically, cranial or craniospinal irradiation was the standard treatment after surgery3 in order to assure that the volume adjacent to the target receives adequate dose and consequently assure local control. However, recent publications have shown that conformal, intensity‐modulated (IMRT) and proton‐beam radiotherapy can achieve similar local control rates to those published in historical publications without an increased risk of marginal failure 4, 5, 6, 7…”
Section: Introductionmentioning
confidence: 97%
“…71,72 Initial studies have shown that protons have comparable local control to photons; however, further information on comparing late toxicities has not been reported. 73 Nonetheless, recent series evaluating neurocognitive data in pediatric patients with localized ependymoma treated with photon RT have shown significantly improved outcomes with minimal impairment. 74,75 Proton RT may also be of benefit in patients receiving craniospinal RT in reducing the dose to structures in front of the spine such as the heart, lungs, bowel, breasts, and thyroid.…”
Section: Treatment Technique and Late Toxicitymentioning
confidence: 99%